Utilization of Marble Wastes in Clay Bricks: A Step towards Lightweight Energy Efficient Construction Materials - Zeeshan Khan; Akhtar Gul; Syed Azmat Ali Shah; Samiullah Qazi; Nauman Wahab; Eid Badshah; Tayyab Naqash; Khan Shahzada (Civil Engineering Journal, 2021)
Marble dust is one of the hazardous byproducts of marble-processing factories and requires planned disposal. Its beneficial use as a construction material will add to the sustainability, and most importantly, might overcome the burden of marble waste disposal. However, the use of marble dust in concrete has a negative impact. Therefore, this research examines various properties related to the utilization of such material in ceramic clay, and therefore its effects on the use of clay bricks are investigated. The research activity covers the categorization of marble dust powder from three different sources: Ziarat in Mohmand Agency, Buneer, and Mullagori (Pakistan). Its utilization in different proportions preparation of bricks is also addressed. Through the partial replacement of clay with marble dust from 0 to 30% by weight with amplification of 5%, seven mix designs are examined. The test result includes Bulk density, water absorption, porosity, thermal insulation, and strength. The partial replacement of clay with marble dust reduced its weight, strength and increased its porosity, water absorption, and thermal insulation. Furthermore, the utilization of marble powder in bricks minimizes soil erosion and reduces pollution to the environment. Doi: 10.28991/cej-2021-03091738 Full Text: PDF